Comfort assessment of high‐rise timber buildings exposed to wind‐induced vibrations. (10th June 2021) - Lazzarini, Enrico; Frison, Giovanni; Trutalli, Davide; Marchi, Luca; Scotta, Roberto
Summary: The current trend of increasing the height limits of timber buildings makes wind‐induced vibrations a non‐negligible issue. The dynamics of high‐rise timber structures are discussed, focusing on accelerations and comfort assessment of the currently tallest timber building in the world, namely, the 18‐storey timber building in Norway. Verifications according to available standards were firstly carried out. Then, computational fluid dynamic analyses with Kratos Multiphysics were performed to simulate the wind flow around a rigid body. Afterward, the wind loads were applied to a single‐degree of freedom model and to a reduced finite element model, performing a one‐way coupling between the wind flow and the structure. Wind‐induced vibrations resulted particularly strong in the across‐wind direction, which is the most sensitive to the wind flow and the shape of the building. Provisions in international standards resulted to be not always enough to avoid discomfort in the occupants. Therefore, fluid dynamic analyses are suggested to simulate the actual response and verify the comfort criteria of tall timber buildings susceptible to wind‐induced vibrations.